Reconstructing the evolution of Lake Bonney, Antarctica using dissolved noble gases. (July 2015) - Warrier, Rohit B.; Clara Castro, M.; Hall, Chris M.; Kenig, Fabien; Doran, Peter T.
Highlights: Estimated water ages using dissolved crustal 4 He and 40 Ar excesses in Lake Bonney (LB). 4 He and 40 Ar excesses identify addition of subglacial discharge from Taylor Glacier. Numerous factors capable of affecting water residence times are evaluated. Maximum 4 He, 40 Ar ages in West LB of 250 kyrs; maximum 4 He age in East LB 27 kyrs. Established chronology appears to correspond to regional and global climatic events. Abstract: Lake Bonney (LB), located in Taylor valley, Antarctica, is a perennially ice-covered lake with two lobes, West Lake Bonney (WLB) and East Lake Bonney (ELB), which are separated by a narrow ridge. Numerous studies have attempted to reconstruct the evolution of LB because of its sensitivity to climatic variations and the lack of reliable millennial-scale continental records of climate in this region of Antarctica. However, these studies are limited by the availability of accurate lacustrine chronologies. Here, we attempt to better constrain the chronology of LB and thus, the evolution of past regional climate by estimating water residence times based on He, Ne and Ar concentrations and isotopic ratios in both WLB and ELB. 3 He and 4 He excesses up to two and three orders of magnitude and 35–150 times the atmospheric values are observed for WLB and ELB samples, respectively. In comparison, while measured 40 Ar/ 36 Ar ratios are atmospheric (∼295.5) in ELB, WLB samples display 40 Ar/ 36 Ar ratios of up to ∼315 reflecting addition of radiogenic 40 Ar. Both 4 He and 40 Ar excesses clearly identify the addition of subglacial discharge (SGD) from underneath Taylor Glacier into WLB at depths of 25 m and 35 m. He isotopic ratios suggest that He excesses are predominantly crustal (>93%) in origin with small mantle contributions (<7%). These crustal 4 He and 40 Ar excesses are used together with basement rock production rates of these isotopes to derive first-order approximations of water residence times for both lobes. Numerous factors capable of affecting water residence times are evaluated and corrected 4 He and 40 Ar water ages are used to place further constrains into the reconstruction of both WLB and ELB history. Combined 4 He and 40 Ar ages in WLB suggest maximum water residence times of ∼250 kyrs BP. These results support the presence of remnant water from proglacial lakes that existed during Marine Isotope Stage 7 (160–240 kyrs) in WLB, in agreement with previous studies. In comparison, 4 He ages in ELB are much younger (<27 kyrs BP) and display a complex evolutionary history that is very different from WLB. 4 He ages also suggest that the ELB ice cover formed significantly earlier (∼1.5 kyrs BP) than previously reported. The timing of these hydrologic changes in ELB appears to correspond to regional and global climatic events that are recorded in both the Taylor Dome ice-core record as well as in other Dry Valley Lakes.